The Changing Role of Student Housing as Social Infrastructure - Franz, Yvonne (2022)
The role of student housing within social infrastructure provision is arguably overlooked. This is a vital issue, as purpose-built student accommodation provides a significant stock of affordable accommodation for students in European university cities while also supporting their social integration in the urban environment. Although an increasing involvement of for-profit student home developers and providers has been diversifying the landscape of student housing across European university cities in the last decade, this change has been mainly associated with the internationalisation of students’ mobility and the financialisation processes driven by private investors. Subsequently, this article expands these supply and demand side perspectives by localising student housing as social infrastructure. Using Vienna as a case study, the authors mapped purpose-built student accommodation locations and conducted qualitative interviews to analyse recent changes in the provision of student housing and to discuss its implications for the social dimension of purpose-built student accommodation. Accordingly, the respective analysis identifies different logics of student housing providers concerning expansion plans and housing quality, which, in turn, affect the function of student housing as social infrastructure. As a result, this article emphasises the need to critically reflect on the overlooked role of student housing as social infrastructure and the role of public actors as well as their policies in the financialisation of purpose-built student accommodation.